The absence of the family in the learning process of reading comprehension: the experience in three groups Primary Education - González Araya, María Nidia (2020)
The present article is the product of a qualitative study about the influence of TIC and other cultural mediators in the process of reading comprehension at the great school level. Despite the fact that this study purported to attain a series of objectives, in the specific case of the present article, only one of them is developed. Such and objective aimed to recognize the level of participation of the family in the promotion of reading in their children. Participants were ten teachers from three educational institutions at the great school level and six fourth and sixth level groups from educational institutions from two Regional School Districts from the West and Alajuela. Likewise, forty-eight parents of these children participated. The main data collection techniques used included questionnaires for the families, teacher interviews and participant observations to the groups. In accordance with the afore mentioned objective, results were that family involvement in the learning of linguistic abilities such as reading is scares or none in some cases. This is evidence to the limited support children have in the reading process on the part of their families, which results in a minimal development of reading abilities, in the limited understanding of texts and low academic performance.